2007
DOI: 10.1016/j.juro.2007.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Fact or Fiction—Is Abuse Prevalent in Patients With Interstitial Cystitis? Results From a Community Survey and Clinic Population

Abstract: Our study demonstrates an association between interstitial cystitis and abuse. Thus, it is important for clinicians to assess for abuse in women with interstitial cystitis or pelvic pain and provide appropriate referral to psychologists or other health care workers to provide comprehensive care for managing their symptoms. Further research is needed to evaluate the role of biopsychosocial therapies, in addition to traditional interstitial cystitis medical therapies for women with a history of abuse and interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 15 publications
2
37
0
2
Order By: Relevance
“…When the McGill pain descriptors were evaluated separately, the sensory component of pain was more predominant in the IC/BPS patients reporting sexual abuse compared to those without, perhaps adding some credibility to the other arguments regarding possible associated mechanisms. 2,3 Similar to the weak association with depression and physical quality of life, these relationships with sexual abuse became nonsignificant when appropriate statistical adjustments were performed for multiple tests. We further noted that there appeared to be a similar weak impact of childhood sexual abuse on depression, anxiety, stress, mental quality of life, social interaction in the non IC/BPS control group; again, when the appropriate statistics were applied, these apparent associations were not statistically significant.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…When the McGill pain descriptors were evaluated separately, the sensory component of pain was more predominant in the IC/BPS patients reporting sexual abuse compared to those without, perhaps adding some credibility to the other arguments regarding possible associated mechanisms. 2,3 Similar to the weak association with depression and physical quality of life, these relationships with sexual abuse became nonsignificant when appropriate statistical adjustments were performed for multiple tests. We further noted that there appeared to be a similar weak impact of childhood sexual abuse on depression, anxiety, stress, mental quality of life, social interaction in the non IC/BPS control group; again, when the appropriate statistics were applied, these apparent associations were not statistically significant.…”
Section: Discussionmentioning
confidence: 88%
“…25 Peters and colleagues documented that 17.7% of IC/BPS patients versus 8.2% of control subjects reported a history of sexual abuse. 2 Clemens and colleagues 26 found that women with IC in a population-based study were 9 times more likely to have a diagnostic code for child abuse (which includes sexual abuse, but also physical and emotional abuse) than agematched controls. In their selected cohort of women with IC/BPS, Seth and colleagues found that 25% of women who reported a history of sexual abuse appeared to have a different clinical presentation than those with no reported abuse history.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Several studies have reported an association between IC and sexual, physical, and emotional abuse. 32 Familial occurrence of PBS is suggested by a study that found that adult female first-degree relatives of patients with IC may have a prevalence of IC 17 times that found in the general population. A greater concordance of IC among monozygotic than dizygotic twins also has been described.…”
Section: Risk Assessmentmentioning
confidence: 99%